The Gains from Agricultural Groundwater Trade and the Potential for Market Power: Theory and Application. Issue 3 (28th January 2020) - Bruno, Ellen M.; Sexton, Richard J.
Abstract : This article models and estimates the efficiency gains from using market‐based instruments relative to command and control to manage groundwater. A theoretical model of an imperfectly competitive groundwater market is developed to show how the magnitude and distribution of the gains from trade change as market structure varies. Market structure is a key consideration because future groundwater markets will likely feature geographic limitations to trade, large agricultural players, and a legal environment that is conducive to forming cartel‐like coalitions. Application of the model to a groundwater‐dependent agricultural region in southern California shows the existence of large gains from trade, despite the potential for market power, with benefits up to 36% greater than that under command and control. Distributional impacts, however, can be sizable even for small degrees of market power. Simulations that vary market conditions show that results likely generalize to other groundwater basins.